A Case Report on Juvenile Ossifying Fibroma Unveiling the Pivotal Role of its Prompt Diagnosis - Amakcham Nita; Kavleen K. Sethi; Haider Iqbal; Anuj Mishra; Tanmay Srivastava; Sparsh Srivastava (Journal of Pharmacy and Bioallied Sciences)
The benign, bone-forming tumor referred to as juvenile ossifying fibroma (JOF) predominantly affects children and teenagers. JOF is an aggressive variety of ossifying fibroma of the jaw, which exhibits a high proclivity for relapse and presents a broad clinical spectrum. A fibro-osseous lesion comprising bands of cellular osteoid trabeculae, huge cells, and cell-rich fibrous tissue is identified as a JOF. Benign mesenchymal skeletal tumors designated as fibro-osseous lesions originate when normal bone is replaced, to varying amounts, by mineralized tissue, blood vessels, and gigantic cells. For the effective intervention of JOF, swift identification and immediate intervention are crucial. This case report recounts the JOF in a 17-year-old girl who presented with classic clinical, radiological, and histological signs of a growing swelling that caused disfigurement on the left side of her face, persistently present for two years. A surgical extirpation was executed and is being monitored to avert recurrence.